Zoneamento (geo)ambiental analítico da microbacia do Córrego do Rosário (Descalvado, SP) - Inêz, Eliezer Bernardes (Universidade Federal de São Carlos, 2012)
Adopting a river basin as a landscape management unit constitutes a major achievement in planning and management due to socio-environmental interactions and their unfoldings that take place in this area. Among the variety of environmental planning and management tools used in river basin contexts, (geo)environmental zoning is noteworthy in that it helps decision makers and aims at reconciling socio-economic development with environmental quality. Along these lines, the purpose of this study focused on the microbasin of the Rosário stream in Descalvado, SP, Brazil was to present an analytical (geo)environmental zoning proposal generated from a set of thematic mapping documents at a 1:10000 scale, field studies, and geo-technologies that seeks to analyze capacities and susceptibilities of this microbasin terrain in the face of urban occupation. Thus, the findings of this study can serve as a basis for discussion and construction of public policies capable of guiding a right and proper local urban expansion process.
Analytical (geo)environmental zoning of the Rosário stream microbasin (Descalvado, SP, Brazil)
Keywords: Planejamento físico-ambiental; Bacia hidrográfica; Zoneamento (geo)ambiental; Expansão urbana; River basin; Urban expansion; ENGENHARIAS